2015
DOI: 10.1111/bcp.12715
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic testing prior to carbamazepine treatment of epilepsy: patients' and physicians' preferences for testing and service delivery

Abstract: Aim Pharmacogenetic studies have identified the presence of the HLA‐A*31:01 allele as a predictor of cutaneous adverse drugs reactions (ADRs) to carbamazepine. This study aimed to ascertain the preferences of patients and clinicians to inform carbamazepine pharmacogenetic testing services. Methods Attributes of importance to people with epilepsy and neurologists were identified through interviews and from published sources. Discrete choice experiments (DCEs) were conducted in 82 people with epilepsy and 83 neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 21 publications
(47 reference statements)
0
24
0
Order By: Relevance
“…Aim is to capture a comprehensive range of perspectives, and sample size will be determined by data saturation. We anticipate72 76 recruiting a purposive sample of ~30 PWE, with or without an informal carer. Table 1 lists the inclusion and exclusion criteria.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Aim is to capture a comprehensive range of perspectives, and sample size will be determined by data saturation. We anticipate72 76 recruiting a purposive sample of ~30 PWE, with or without an informal carer. Table 1 lists the inclusion and exclusion criteria.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The ordinal ranking across each group will be determined, and those ranked highest will be taken forward for DCE development. We have successfully implemented this method in previous DCEs, [53] and it is consistent with the reductiveness approach of attribute development. [52] We will also pilot the Carer Experience Scale as a means to estimate carer utility.…”
Section: Identification Of Attributes For a Future Discrete Choice Exmentioning
confidence: 68%
“…For many patients, this may represent their first experience receiving a clinical test in a pharmacy setting. Many patients may be more will ing to be tested since there is no cost, but studies have indicated patients' willingness to pay for genetic tests, particularly for older patients, with higher income and perceived clinical and personal utility [56][57][58][59]. A supplemental study to the proposed survey, such as a focus group study, may be of value to gather additional feedback from patients.…”
Section: Discussionmentioning
confidence: 99%